Churchill's mastery of medicine : pharmacology - Winstanley, Peter; Walley, Tom. (New York: Churchill Livingstone, 1996)
A concise core text of clinically relevant pharmacology. The text includes only essential information - so the reader knows the whole book is relevant. Self-assessment material is integral to the book, and has been specially designed to be of maximum benefit to the student during self-directed learning and examination preparation. Scientific information is integrated with the appropriate clinical points. And the illustrations are simple and memorable, making them easy to reproduce during examinations. This is a volume in the Churchill's Mastery of Medicine series - a major new series for medical students. For the above-average student, this text will be a valuable learning and review book, going alongside the major textbooks. For the less able, it will be ideal as the sole book to define the essential core of the subject and to ensure that it is understood by use of the self-assessment material. Features: Part of a major new series -- Presents the essential core of the subject -- Integrates basic science and clinical pharmacology -- Ideal for self-directed learning Diagrams ideal for reproducing in exams -- Self-assessment material tests readers' understanding -- Perfect for exam revision.
DC010226
In English
Keywords: Pharmacology; Clinical Therapeutics; Pharmacology -- Textbooks; Pharmacology -- Textbooks; Clinical pharmacology -- Textbooks